Ionized Envelopes Around Protoplanets and the Role of Radiative Feedback in Gas Accretion - Matías Montesinos; Juan Garrido-Deutelmoser; Jorge Cuadra; Mario Sucerquia; Nicolás Cuello; Matthias R. Schreiber; María Paula Ronco; Octavio M. Guilera (The Astrophysical Journal)
Planetary growth within protoplanetary disks involves the accreting of material from their surroundings, yet the underlying mechanisms and physical conditions of the accreting gas remain debated. This study aims to investigate the dynamics and thermodynamic properties of accreting gas giants, and to characterize the envelope that forms near the planet during accretion. We employ 3D hydrodynamical simulations of a Jupiter-mass planet embedded in a viscous gaseous disk. Our models incorporate a nonisothermal energy equation to compute gas and radiation energy diffusion and include radiative feedback from the planet. The results indicate that gas accretion occurs supersonically toward the planet. The ionized envelope extends from the planetary surface up to 0.2 times the Hill radius in the no-feedback model, and up to 0.4 times the Hill radius in the feedback model. The envelope’s radius, or ionization radius, acts as a boundary halting supersonic gas inflow and is pivotal for estimating accretion rates and H α emission luminosities. Including radiative feedback increases the accretion rates, especially within the ionization radius and from areas to the right of the planet when the star is positioned to the left. The accretion luminosities calculated at the ionization radius are substantially lower than those calculated at the Hill radius, highlighting potential misinterpretations in the nondetection of H α emissions as indicators of ongoing planet formation.